You are on page 1of 3

# Model on Laplace transform method for IVP for ODEs

Solve
y 00 + y = sin x, y 0 (0) = 0, y(0) = 1. (1)
Taking Laplace transforms,
1
s2 Y − y 0 (0) − sy(0) + Y =
s2 +1
which gives after incorporating the values of y(0) and y 0 (0),
s 1
Y = + 2 = L(cos t) + L(?) (2)
s2 + 1 (s + 1)2

We now proceed to find the function that fits in the slot marked (?) namely we need a function whose
Laplace transform is precisely (1 + s2 )−2 . This is not such a merry exercise if we insist on working
with sines and cosines as we now proceed to demonstrate. The situation must be compared with the
earlier case of Method of Undetermined Coefficients where working with exp(it) and exp(−it) was far
more efficient. Recall
a s
L(sin at) = 2 2
, L(cos at) = 2
s +a s + a2
Differentiating these with respect to a we get the following:

s2 − a2 2sa
L(t cos at) = , L(t sin at) =
(s2 + a2 )2 (s2 + a2 )2

## Let us rewrite the first of these as

s 2 − a2 s2 + a2 − 2a2  sin at  2a2
L(t cos at) = = = L −
(s2 + a2 )2 (s2 + a2 )2 a (s2 + a2 )2

So finally
1  sin at t cos at 
= L − (3)
(s2 + a2 )2 2a3 2a2
So now (2) can be written as:
 sin t t cos t 
Ly = Y = L cos t + −
2 2
Solution of (1) is then
sin t t cos t
y(t) = cos t + − (4)
2 2

Exercise: Solve y 00 + y = x sin x, y(0) = 1, y 0 (0) = 0. Expect to see a 1/(s2 + 1)3 and look for a
function whose Laplace transform is (1 + s2 )−3 . Good luck with the search.

## Use of exponentials greatly simplifies life:

Our problem is
1
Y = L(cos t) +
(s2 + 1)2

1
Use partial fractions:
1 A B C E
= + + + (5)
(s2 + 1) 2 s − i (s − i) 2 s + i (s + i)2
Obviously C, E are the complex conjugates of A and B respectively. Multiply (5) by (s − i)2 and let
s −→ i and we get
B = −1/4 = E.
Now that we have found B we can subtract the term B/(s − i)2 from both sides of (5) and we get

1 n 1 1o A C E
2 2
+ = + + (6)
(s − i) (s + i) 4 s − i s + i (s + i)2

## Now multiply (6) by (s − i), let s −→ i and we get

1 n 1 1o n −2 o −i
A = lim + = lim = = C.
s→i (s − i) (s + i)2 4 s→i (s + i)3 4

## Needless to say YOUR FAVOURITE L’Hospital’s rule has been employed !

So we have now
1 1 1  1 1 1 
Ly = Y = L(cos t) − + + − (7)
4 (s − i)2 (s + i)2 4i s − i s + i

Now recall that L(eat ) = 1/(s − a) and so by differentiating with respect to a repeatedly we get
1 2
L(teat ) = , L(t2 eat ) = (8)
(s − a)2 (s − a)3

## Hence using (8) with a = i we rewrite (7) as:

 sin t t cos t 
Ly = L cos t + − .
2 2
which gives
sin t t cos t
y(t) = cos t + − .
2 2

2
Find the inverse Laplace transform of
s + a
F (s) = log (9)
s+b
Let f (t) be the function whose Laplace transform is (9). Then,

## −F 0 (s) = L(tf (t))

so that
1 1
L(tf (t)) = − = L(e−bt − e−at ).
s+b s+a
Hence
1
f (t) = (e−bt − e−at ).
t